Comparison of Selected CD45(+) Cell Subsets’ Response and Cytokine Levels on Exhaustive Effort Among Soccer Players - Kostrzewa-Nowak, Dorota (J Med Biochem, 2019)
BACKGROUND: Immunological alterations may led to the reduction in capacity and endurance levels in elite athletes by e.g. increased susceptibility to infections. There is a need to explain the impact of intensive physical effort on the CD4(+) memory T cell subsets. METHODS: Fourteen participants median aged 19 years old (range 17–21 years) were recruited form Pogoń Szczecin S.A., soccer club. They performed progressive efficiency test on mechanical treadmill until exhaustion twice: during preparatory phases to spring and autumn competition rounds. We examined the influence of exhaustive effort on the selected CD45(+), especially CD4(+) memory T cell subsets and inflammation markers determined before, just after the test and during recovery time. RESULTS: Significant changes in total CD45(+) cells and decrease in T lymphocytes percentage after the run was observed. Significant fluctuations in T cells’ distribution were related not only to the changes in Th or Tc subsets but also to increase in naïve T cell percentage during recovery. Increase in TNF-α and IL-8 post-exercise, IL-6 and IL-10 plasma levels in recovery was also found. CONCLUSIONS: The novel finding of our study is that the run performed on mechanical treadmill caused a significant release of CD4(+) T naïve cells into circulation. Post-exercise increase in circulating NK cells is related with fast biological response to maximal effort. However, at the same time an alternative mechanism enhancing inflammation is involved.